Kony 2012 : ativismo civil e a vida moral no cibermundo - Pereira, Guilherme Mendes (2014)
This dissertation investigates the moral issues related to the circulation of humanitarian campaign KONY 2012 on the Internet, which was created by the organization Invisible Children (IC) in 2012. This campaign has asked people to request international authorities for military support to the Uganda s government so it can extinguish the actions of Joseph Kony, a leader of a movement responsible for the committal of many heinous crimes. This research is justified by the need to understand the cyber mediated communication and cultural phenomena, which put to the test modes of socialization and political organization, ethical standards and moral positions. Thus, this study is developed with observations and historical and sociological confrontations, seeking to understand the ambiguities and paradoxes of contemporary socialities. Based on methodological perspective indicated by Rüdiger (2011), this phenomenon is studied in two axes: movement and countermovement. The KONY 2012 movement consists in audiovisual productions and text comments that were important to the popularization of the cause. In its turn, the countermovement KONY 2012, in addition of severous audiovisual productions and text comments, also consists of actions that denied the campaign. To conduct the reflections about this subject, this study was guided by theoretical discussions about morals and morality in the postmodern world, based in Giddens (1991), Lipovestky (1994), Vattimo (1994) and Bauman (1997) perspectives. In this investigation, we realized that the movement and countermovement KONY 2012 showed that, despite the apparent unquestionability of the cause, the moral responsibility in the postmodern context remains complex and problematic. On the one hand, it records the possibility of free encounter with other worlds and ways; of the enjoyment of the free will, as an oscillatory experience between belonging and rootlessness in the society of generalized communication. On the other hand, the situation of morality in this context reveals the irresponsibility of subjects: the experimentation and the everyday spontaneous fruition, of the being and of the living on the basis of aesthetic sense, seem to be the best interests. Thus, we discuss that the said emancipatory technologies are not favorable when there is lack of awareness and moral responsibility.